Escore de Valor em Saúde (EVS): Uma proposta para mensuração de valor dentro de um sistema de saúde. - Lacerda Abicalaffe, César Luiz; Branco de Araujo, Gabriela Tannus; de Oliveira Ribas, Luiz Fernando; da Silva Cabral, Ângelo (JBES: Brazilian Journal of Health Economics / Jornal Brasileiro de Economia da Saúde)
A value-based healthcare system must deliver the best possible patient outcomes, outcomes that really matter to the patient, at the lowest possible cost. The concept is relatively easy to understand, but the metric to demonstrate it has been a major challenge for healthcare systems. This article demonstrates the creation of a Health-Based Health Care Score (EVS) using Multi-Criteria Decision Analysis which can be applied in any health system to evaluate professionals, healthcare providers and care pathways for patients with a specific disease.